2021
DOI: 10.1155/2021/7118464
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Levels of PDGF, EGF, and sFlt-1 in Patients with Polycystic Ovary Syndrome and Their Predictive Effects on Pregnancy Outcomes

Abstract: Polycystic ovary syndrome (PCOS) is a neuroendocrine disease with complex etiology characterized by infrequent menstruation, follicular developmental disorders, insulin resistance, and hyperandrogenism. PCOS patients often suffer from anovulatory infertility, and even after successful pregnancy promotion, spontaneous abortion is easy to occur. At present, PCOS is mainly diagnosed by auxiliary examinations such as sex hormones and B ultrasonography, and there is a lack of specific serological markers for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Epidermal growth factor (EGF) is a protein that stimulates cell growth, differentiation, and survival by binding to its receptor, EGFR [ 27 ]. Only a recent study has suggested a role for EGF in insulin resistance, showing an abnormal serum level in women with polycystic ovary syndrome [ 28 ]. Another study also indicates that elevation of EGF may play a role in the induction of obesity in mice after ovariectomy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) is a protein that stimulates cell growth, differentiation, and survival by binding to its receptor, EGFR [ 27 ]. Only a recent study has suggested a role for EGF in insulin resistance, showing an abnormal serum level in women with polycystic ovary syndrome [ 28 ]. Another study also indicates that elevation of EGF may play a role in the induction of obesity in mice after ovariectomy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the importance of EGFR in meiotic maturation of the oocyte has been reported in recent years. For example, Gao et al showed that the level of serum EFG in the abortion PCOS patients was higher than that in the successful delivery PCOS patients, moreover, EFG was an independent factor which affecting and positively correlated with the pregnancy outcome of PCOS patients (26). Mechanistically, in a recent study by Wu and colleagues, they found that high expression of microRNA-194 in granulosa cell of PCOS patients could induce KGN cells apoptosis by direct targeting heparinbinding EGF-like growth factor (27).…”
Section: Discussionmentioning
confidence: 99%
“…Özcan et al [526], Emokpae et al [527], Batista et al [528], Darbari et al [529], ElAlfy et al [530], Hounkpe et al [531], Vogel et al [532], Afifi et al [533], Shmukler et al [534], El Sissy et al [535], Cavalcante et al [536], Sadler et al [537], Kalai et al [538], Silva et al [539], Jhun et al [540] and Cai et al [541] that ALB (albumin), LPL (lipoprotein lipase), KL (klotho), UGT2B7, IFNG (interferon gamma), MPO (myeloperoxidase), BTK (Bruton tyrosine kinase), CD209, KCNN4, CCR5, TNF (tumor necrosis factor), CCR2, CCL5, NOS3, S100B and HBB (hemoglobin subunit beta) are associated with progression of sickle cell disease. Studies showed that altered expression of MTNR1A [542], GATA6 [543], EGF (epidermal growth factor) [544], LPL (lipoprotein lipase) [545], PPARGC1A [546], ERBB4 [547], KL (klotho) [548], GCLC (glutamate-cysteine ligase catalytic subunit) [549], NOX4 [550], SORCS1 [551], FKBP5 [552], CCNL1 [553], USP25 [554], SAA1 [555], MPO (myeloperoxidase) [556], GATA1 [557], LCN2 [558], IL1RN [559], IL11 [560], PDCD1 [561], TNF (tumor necrosis factor) [562], TNFRSF1B [563], APLNR (apelin receptor) [564], COMP (cartilage oligomeric matrix protein) [565], RETN (resistin) [566] and IGFBP1 [567] were associated with the progression of polycystic ovarian syndrome. Combined with the results of GO and REACTOME pathway enrichment analysis, these results imply these genes might participate in FSGS.…”
Section: Discussionmentioning
confidence: 99%